(untitled) (Asian Journal of Agriculture, 2019)
Abstract. Bidgoli RD. 2019. Effect of inoculation of two Aztobacter and nitrogen fertilizer on of peppermint (Mentha piperita) essential oil. Asian J Agric 3: 22-25. This study was conducted to study changes of percentage and yield of essential oil of peppermint (Mentha piperita) as a split factorial in a randomized complete block design (RCBD) with three replications in 2016-2017. The experimental treatments were nitrogen at four levels 0, 50, 100 and 150 kg/ha as the main factor and two strains of PGPR (Azotobacter chroococcum MZ11, MZ26) in two states of (use and non-use) was considered as subfactors. Results showed that use of these two A. chroococcum strains has led to an increase in the percentage and yield of peppermint essential oil more than all Nitrogen fertilizer treatments. Also, the highest peppermint essential oil percentage (0.73%) was obtained in the triple interaction of Nitrogen (100 kg/ha) A. chroococcum MZ11 and A. chroococcum MZ26. The highest essential oil yield (91.65 kg/ha) was observed under the influence of the triple interaction of Nitrogen (100 kg/ha), A. chroococcum MZ11 and A. chroococcum MZ26.